Cellular senescence is a promising target for chronic wounds: a comprehensive review. Issue 1 (23rd June 2020) - Wang, Ziwen; Shi, Chunmeng
Abstract: Chronic wounds include, but are not limited to, radiation ulcers, pressure ulcers, vascular ulcers and diabetic foot ulcers. These chronic wounds can persist for years without healing and severe ulcers may lead to amputation. Unfortunately, the underlying pathologies of refractory chronic wounds are not fully characterized, and new treatments are urgently needed. Recently, increasing evidence has indicated that cell senescence plays an important role in the development of chronic wounds, and preventing cell senescence or removing senescent cells holds promise as a new therapeutic strategy. In this review, we aim to probe these latest findings to promote the understanding of cellular senescence in the pathological process and potential management of chronic wounds.